Interferences of Spanish on students' English production at Experimental-Bilingual High Schools of The Western Region : a study on interlanguage - Chavarría Madrigal, Carlos Darío 1979- (2022)
7 Abstract In the present study, the most relevant Spanish interferences related to grammar were examined and interpreted as well as the implications they had on students' English proficiency. Several studies and two theories were considered to explain interference on SLA, the Complexity Theory and Interlanguage. Our research addressed the following question: What are some of the most common errors as mother tongue interferences shown by tenth- graders from The Western Region when they speak English? In this case study, teachers and students partook in oral interviews; data was collected and results were thoroughly examined. That data collected demonstrated how the target language affected the acquisition of a second language. Main findings pointed out at the perception of three recurring types of mistakes: Misuse of third person singular, incorrect syntax, and negative word transfer. Consequently, these mistakes came to be related to translation of structures, lack of exposure to English, and negative transfer. Some of the authors that theoretically backed up this study on interference focused their arguments mainly on studies made with adult populations, but the population studied in this instance were teenagers so there is a chance for the results to vary.